Trastorno mixto ansioso depresivo en los pacientes de los Centros de Atención Privada del cantón Loja - Novillo Tacuri, María José (2019)
The mixed anxious-depressive disorders are very frequent, they are among the main causes of disability in the world and they are also responsible for a significant personal burden, as well as a high cost in health. The purpose of this research is to identify the mixed anxiety depressive disorder in the adult population of the private Clínica de Especialidades Mogrovejo, the levels of anxiety and depression before and after receiving the combined treatment. This is a non-experimental, cross-sectional, descriptive, prospective design study, in which the Beck depression scale was applied to measure depression levels and the Hamilton anxiety scale to measure anxiety levels at the time of consultation and after 3 months of comprehensive pharmacological and psychological treatment. The sample consisted of 120 patients, the following results were obtained: 68.3% patients diagnosed are between 20 to 40 years of age and 31.7% between 41 to 60 year old. According to gender, it is more frequent in women 61.7%. At the beginning they presented symptoms of anxiety and severe depression; after combined treatment: 27.5% absence of anxiety, 50.0% mild anxiety and 22.5% moderate anxiety. While, 57.5% absence / minimal depression, 38.3% mild depression and 4.2% moderate depression. In conclusion, the symptoms of anxiety and depression decreased compared to those presented in the first consultation. Key words: Beck depression scale, Hamilton anxiety scale, combined treatment.